Phylogenetic Structure and Comparative Genomics of Multi-National Invasive Haemophilus influenzae Serotype a Isolates - Topaz, Nadav (2022)
Recent reports have indicated a rise of invasive disease caused by Haemophilus influenzae serotype a (Hia) in North America and some European countries. The whole-genome sequences for a total of 410 invasive Hia isolates were obtained from 12 countries spanning the years of 1998 to 2019 and underwent phylogenetic and comparative genomic analysis in order to characterize the major strains causing disease and the genetic variation present among factors contributing to virulence and antimicrobial resistance. Among 410 isolate sequences received, 408 passed our quality control and underwent genomic analysis. Phylogenetic analysis revealed that the Hia isolates formed four genetically distinct clades: clade 1 (n = 336), clade 2 (n = 13), clade 3 (n = 3) and clade 4 (n = 56). A low diversity subclade 1.1 was found in clade 1 and contained almost exclusively North American isolates. The predominant sequence types in the Hia collection were ST-56 (n = 125), ST-23 (n = 98) and ST-576 (n = 51), which belonged to clade 1, and ST-62 (n = 54), which belonged to clade 4. Clades 1 and 4 contained predominantly North American isolates, and clades 2 and 3 predominantly contained European isolates. Evidence of the presence of capsule duplication was detected in clade 1 and 2 isolates. Seven of the virulence genes involved in endotoxin biosynthesis were absent from all Hia isolates. In general, the presence of known factors contributing to β-lactam antibiotic resistance was low among Hia isolates. Further tests for virulence and antibiotic susceptibility would be required to determine the impact of these variations among the isolates.